Effects of Channels of Communication on Female Literacy - Afzal, Mahira; Dr. Muhammad Zakria Zakar (Journal of Peace, Development and Communication, 2021)
This research explores possible avenues to accelerate female literacy through channels of communication as means of knowledge and information. 500 female respondents aged 14 years and above residing in Lahore district of Punjab, were selected based on random sampling technique. The study shows that channels of communication are successful streams and effective tools for enhancing female literacy. Females despite being literate still face socio-cultural barriers to access information and knowledge. The analysis shows that channels of communication particularly newspaper and magazine/digest are major contributing factors in enhancement of female literacy and education. Varied levels of effects on enhancement of literacy and education are recorded in case of mass media and IPC, when analyzed together. Literate female can access newspaper and magazine/digest more easily than TV and radio. Medium of information and knowledge with regard to literacy is proved to be mass media and IPC with varied degrees.